An analysis of extreme temperature events (ETEs) of Namibia - Steyn, Christiaan (University of the Witwatersrand, Johannesburg, 2021)
Heatwaves, warm spells, cold waves, and cold spells are examples of extreme temperature events (ETEs) that have catastrophic consequences for human health and ecosystems. Climate change is expected to increase the frequency, intensity, and length of ETEs. Effective adaptation to ETEs necessitates an appreciation of their current frequency and likelihood of occurrence in the face of climate change. Extreme events have received very little attention, especially in developing countries, including Namibia. Due to Namibia’s low adaptive ability, urgent development needs, and relatively poor infrastructure, these events pose a significant danger. This research examines extreme weather events over time, both annually and seasonally, as well as spatially over the period 2008-2018. The World Meteorological Organisation Expert Team on Climate Change Detection (ETCCDI) and the World Meteorological Organisation Commission for Climatology and Indices Expert Team on SectorSpecific Climate Indices (ET-SCI) were used to determine ETEs, using ClimPACT and RClimDex. The non-parametric Mann-Kendall, Spearman Rank Correlation Coefficient, and Sen's slope estimates were used to quantify trends. Annual and seasonal cold spell duration were identified as 4.86 days. An average of 1.99 cold waves was identified with an average duration of 4.59 days. The results identified an average number of heatwaves of 1.6 lasting 3.2 days. The majority of ETEs occur in the central, northeast and southeast of the country. The west coast has experienced ETEs, but with less intensity. Since studies indicate that unusually temperature events may persist in a warming world, these findings help raise awareness and recognise the frequency and length of extreme events in Namibia.
A dissertation submitted in fulfilment of the academic requirements for the degree of Master of Science (MSc) to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021
Keywords: Extreme temperature events (ETEs); Climate changes; Temperature; SDG-13: Climate action